MENGGALI SINERGI DAN KETEGANGAN PRINSIP EKONOMI ISLAM DENGAN DINAMIKA EKONOMI DIGITAL - Teguh Prakoso (Prosiding Seminar Nasional Indonesia, 2023)
This study explores the potential synergies and tensions between Islamic economic principles and the dynamics of the digital economy. The study begins with an overview of Islamic economic principles and their relevance in the contemporary business landscape. This chapter then examines the dynamics of the digital economy, including the rise of e-commerce, fintech, and social media, and their implications for Islamic finance and banking. The paper also discusses potential tensions between these two domains, such as the role of interests, privacy concerns, and regulatory challenges. Furthermore, this study presents case studies of companies and initiatives that incorporate Islamic economic principles in the digital economy. The paper concludes with implications and recommendations for policy makers, businesses, and other stakeholders as well as suggestions for future research. Therefore, this research provides valuable insights into the intersection between the Islamic economy and the digital economy and offers a framework for understanding how the two can work together to drive growth and innovation.